Efect of Bitter Melon (Momordica charantia) and Bitter (Andrographis paniculata) Extract to Humoral Immunity in Balb/c Mice Model of Type 2 DM - Lailiya Vina Rochmatika; Muhaimin Rifa'i (University of Brawijaya, 2015)
ABSTRACT Type 2 diabetes mellitus (DM2) is disease caused by decreased insulin receptor sensitifity, so that, causing level blood glucose to rise. One of strategy to reduce blood glucose level is by administration with medicinal herbs. The aim of this research was to analyze the effect of bitter melon (Momordica charantia) and bitter (Andrographis paniculata) extract on B220 cell in Balb/c mice model of type 2 DM. Mice in the age of 5 days were divided into five groups, each group consists of 4 mice. The treatments consist of negative control (normal mice), positive control (DM2), dose 1, dose 2, and dose 3. DM2 was induced by intraperitoneally injection of Streptozotocin (STZ) in neonate BALB/c mice. Treatment with bitter melon and bitter was performed for 14 days. Blood glucose level was examined by glucometer. Spleen cells were isolated and analyzed by flow cytometry post treatment. The result showed that dose 3 of extract of Bitter (Andrographis paniculata) and Bitter melon (Momordica charantia) can increase the number of B cells in DM2 treated mice compare to DM2 untreated mice. Furthermore, we showed that Bitter melon extract herbal (Momordica charantia) and Bitter (Andrographis paniculata) had an ability to reduce blood glucose level in concentration dependent manner. Dose 3 known as the most efective to optimize either B cells proliferation or blood glucose reduction. Key words: Bitter, bitter mellon, diabetes mellitus type 2, streptozotocin